2015
DOI: 10.1007/s00402-015-2247-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tibial slope in acute ACL-insufficient patients on concurrent meniscal tears

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 45 publications
1
27
0
1
Order By: Relevance
“…Markl et al examined the rate of meniscal tears in found ACL deficient patients and noted increased rates of meniscal tears in with medial and lateral tibial slope greater than 10 (odds ratio 2.11 for medial and 3.44 for lateral slope), however in this small study of only 71 subjects these findings did not reach statistical significance [25].…”
Section: Discussionmentioning
confidence: 63%
“…Markl et al examined the rate of meniscal tears in found ACL deficient patients and noted increased rates of meniscal tears in with medial and lateral tibial slope greater than 10 (odds ratio 2.11 for medial and 3.44 for lateral slope), however in this small study of only 71 subjects these findings did not reach statistical significance [25].…”
Section: Discussionmentioning
confidence: 63%
“…Laxity after ACL injuries increases anterior tibial translation, inducing the medial meniscus to engage into the femoral condyle and act as a wedge against the posterior tibia, resulting in high-stress loading on the meniscocapsular junction. 26,28,30 Moreover, increasing the tibial slope was noted to increase anterior translation in ACLdeficient knees 16,29,40 and increase the incidence of secondary medial meniscal lesions. 26 However, other studies have reported no significant association between tibial slope and medial meniscal lesions.…”
Section: Discussionmentioning
confidence: 96%
“…26 However, other studies have reported no significant association between tibial slope and medial meniscal lesions. 17,30 Moreover, Song et al 40 noted that increased medial meniscal slope was an independent anatomic risk factor for ramp lesions, particularly in patients at >6 months since the time of injury, given the increased excursion of the femoral condyle with anterior translation of ACL-injured knees. However, they indicated that there was no association between medial tibial slope and ramp lesions.…”
Section: Discussionmentioning
confidence: 99%
“…28 Furthermore, several studies have evaluated the association between the PTS and risk of meniscal tears in ACLdeficient knees. 20,21,26 As the MMPH acts as a wedge limiting anterior translation of the tibia in ACL-deficient knees, the stress applied to the MMPH would increase in these knees. 16,26 In this regard, 2 preceding studies reported that an increased sagittal slope of the geometry in the medial tibial plateau was an anatomic risk factor for secondary medial meniscal tears in ACL-deficient knees.…”
Section: Discussionmentioning
confidence: 99%